DYNAMICS OF CHANGE IN UNITED STATES POLICY IN THE SYRIAN CRISIS: ANALYSIS OF THE TRANSITION FROM DIPLOMACY TO INTERVENTION - Fauzi, Wajid; Rochani Adi, Ida; Hindun, Hindun (Pengkajian Amerika, Universitas Gadjah Mada, 2025)
The United States' policy toward the Syrian crisis (2011-2019) was marked by a significant and often inconsistent transition from diplomatic caution to direct military intervention. This article analyzes the dynamics of this policy evolution, moving beyond traditional state-centric explanations to examine the influence of cross-border flows. It argues that the transition was not a linear progression but a reactive and fragmented process driven by the interplay of three key factors: the failure of established international diplomatic mechanisms to resolve the conflict; the transnationalization of the threat landscape with the rise of the Islamic State (ISIS); and the powerful, albeit fluctuating, influence of global media narratives depicting humanitarian atrocities. This study maps the critical junctures that compelled policy recalibration by employing a qualitative process-tracing methodology and discourse analysis of official documents, presidential statements, and media reports. The findings demonstrate that key decisions from the